Analyzing Civic Satisfaction on Public Service Using Twitter Data - Ade Hendraputra (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2017)
In recent years, digital technology has transformed rapidly, allowing social media to become an important place for people to express their thoughts and opinion on any topic that they want. In this paper, we present an analysis of Twitter data regarding civic satisfaction and opinion of public service in Indonesia. We try to capture the tweets which discussed several topics related to traffic condition, public service and driving license service. Then we present an analysis process using a framework and present the result which may help the government have a better picture of certain problems.